KONSEP GREEN MARKETING DAN DAMPAKNYA TERHADAP PERILAKU KONSUMEN INDONESIA - Lu’lu’ul Jannah; Erni Hernawati (Jurnal Bina Manajemen, 2021)
The purpose of this study is to determine the concept of green marketing on Indonesian consumer behavior. The data analysis method was carried out by using regression analysis either partially or simultaneously. The results showed that the attitude and environment partially influenced the involvement of green products, while the attitude environment and the involvement of green products simultaneously influenced the involvement of Indonesian society in purchasing green products in selecting products. And the results of the simultaneous regression analysis from the ANOVA test with a significance level of 0.000. Because the significant probability is much smaller than 0.05, this indicates that simultaneously it states that there is an effect of attitude environment and the involvement of green products simultaneously influencing the involvement of green product purchases.